Sistem Informasi Keuangan Berbasis Web Pada PT PLN UP3 Kotamobagu - Ester Toar; Isni Nintias; Christania Bawole (Program Studi Teknik Informatika, 2020)
Abstract— Pt. PLN (Persero) UP3 Kotamobagu is one of the Customer Service Units under suluttenggo regional parent, as one of the State-Owned Enterprises (SOEs) which aims to generate revenue derived from marketing, electricity sales and operational services. In order to increase the marketing and sale of electricity to the company, then create an information system that is a financial information system. The Research Method used in this study is the Prototype method. Stages are: Needs Analysis, Prototyping Building, Prototyping Evaluation, Coding Systems, Testing Systems, System Evaluation, and Using Systems